3-D Modeling of Historic Façades Using SFM Photogrammetry Metric Documentation of Different Building Types of a Historic Center. Issue 6 (18th August 2017) - Peña-Villasenín, Simón; Gil-Docampo, Mariluz; Ortiz-Sanz, Juan
ABSTRACT: One of the main factors affecting the application of photogrammetric techniques to 3-D modeling is the degree of the space limitations imposed by nearby objects. Numerous studies show the reliability of structure from motion (SFM) when the object is located in a large and accessible space; however, when applying this technique to a particular case, the shooting must be adapted to the peculiarities of each location. This article presents the photogrammetric documentation of façades of different urban typologies, focusing on the photo-shoot arrangement that best enables us to solve the geometrical peculiarities for each case. The historic center of Santiago de Compostela (Spain) has been chosen for this study. Four representative cases of different urban typologies were selected: "significant façade, " "façade on a standard street, " "very narrow street" (width/height < 1/3), and "façade with arcades". All have been resolved satisfactorily, having obtained relative errors between 1/770 and 1/1040.